Rewriting Buddhism: Pali Literature and Monastic Reform in Sri Lanka, 1157-1270, by Alastair Gornall - Appleton, Naomi (Buddhist Studies Review, 2023)
Rewriting Buddhism: Pali Literature and Monastic Reform in Sri Lanka, 1157-1270, by Alastair Gornall. UCL Press, 2020. XIII-269pp. Hb £40, ISBN 9781787355156.